Shifting towards online training-Possible challenges from Educators/Trainers perspective in Indian setting - Singh, Snehil; Gupta , Sanjay; Sharma, Lokesh; Chatterjee , Mainak; Juneja , Sumeet; Panigrahi , Paritosh; Kumar , Hitesh; Thakur , Harshad (Indian Journal of Community Health, 2020)
Worldwide metastasis of novel coronavirus COVID-19 has caused immense alterations among every walk of human existence and social interaction(1). Education and training sector being as vulnerable to these adjustments as any other domain(2). Owing to its extremely infectious nature, the COVID-19 pandemic enforced the closure of training institutes globally. All the traditional classroom training were restricted as an instant consequence, to achieve the norms of social distancing which can perhaps aid in obliterating the infection curve and lessen the resultant fatalities(3). Educational institutions in India predominantly bank on traditional methods of training, utilizing conventional setup of in-person training and lectures in a teaching space. While over the years, there is a marked shift towards blended learning, still most of the academic institutes are guided by the existing orthodox learning methodologies. An unexpected outbreak of the Covid-19 pandemic caused by Corona Virus (SARS-CoV-2) shuddered the entire world (4). This complete shutdown kind of circumstances has tested the education system globally and coerced the educators to shift to digital platforms and online modules almost instantaneously. Academic institutions were required to shift from their traditional pedagogical approach to online teaching-learning. The article recognises the possible barriers to swiftly shift from traditional methods of learning towards e-learning among adult professionals through analysing the limitations faced by the authors while converting and conducting traditional trainings into e-trainings at The National Cold Chain and Vaccine Management Resource Centre (NCCVMRC-NIHFW), New Delhi. This article also put some light on methodologies that could assist academic institutions in dealing with challenges associated with shifting towards e-learning.